Hubungan gambaran CT-Scan paru dengan kadar monosit dan laju endap darah pada pasien SARS-COV-2. - Novianti, Wulan; Anto, Endy Juli; B. Hutagalung , Sanggam (Jurnal Kedokteran Methodist, 2022)
Background : Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is a new type of Coronavirus that is transmitted to humans that attacks the respiratory system and manifests as inflammation of the lung parenchyma. CT Scan can be used as an alternative diagnostic measure to find out the radiological picture of COVID19 patients. monocytes/macrophages can serve as reservoirs which, consequently, will serve as vectors of virus spread to other tissues, but this has not been proven in SARS-CoV-2. Inflammation is an important body mechanism to protect itself from foreign objects. During this process, cells release various proinflammatory cytotoxins, including active-phase proteins such as CRP (C-Reactive Protein) and fibrinogen. Then, the increase in fibrinogen levels further becomes a factor that increases the ESR. Research Objectives: To determine whether there is a relationship between CTScan Lung images and Monocyte Levels and ESR in SARS-CoV-2 patients. Research Methods: The type of research carried out is observational analytic measurement, with a cross sectional design the researcher makes observations or measurements of variables at certain times. Research results: the frequency distribution on CT-SCAN images of the lungs of SARS-CoV-2 patients was found to be the most GGO with a frequency of 22 people (38.6%) and the frequency distribution of monocyte and ESR levels in SARS-CoV2 patients obtained the highest levels of monocytes. in patients with SARS-CoV-2 is normal with a frequency of 35 people (61.4%) and the ESR level is normal with a frequency of 44 people (77.2%). In the analysis, there was a significant relationship between pulmonary CT-SCAN images on monocyte levels and ESR in patients with SARS-CoV-2 p-values = 0.022 and 0.003, and had a simultaneous and partial effect. Conclusion: there is a relationship between CT-SCAN images of the lungs of SARSCoV-2 patients and the levels of monocytes and ESR in the body.